Numerical Analysis on the Ground Vibration Isolation of Duxseal - M. Gao; S. P. Tian; R. He; Y. Wang; Q. S. Chen (Advances in Civil Engineering)
A new kind of vibration screening material, Duxseal, with a high damping ratio is proposed to be used as an active vibration barrier in the free field. To investigate the influence of width, thickness, and embedded depth of using Duxseal on vibration reduction, numerical studies are performed using a three-dimensional (3D) semianalytical boundary element method (BEM) combined with a thin-layer method (TLM). The isolation effectiveness of Duxseal in ground vibration is also compared with the traditional wave impeding block (WIB). The numerical results show that Duxseal performed exceedingly well in screening ground vibrations in the free field. The effectiveness of the vibration isolation increases with the increase in the width, thickness, and embedded depth of the Duxseal material, within a certain range, under harmonic vertical excitation. In addition, Duxseal is much more effective for isolating ground vibration than the traditional WIB. The performance of Duxseal in isolating ground vibration is relatively stable along the distance away from the vibration source, while the amplitude attenuation ratio bounces upward when the distance away from the vibration source increases for the WIB isolation system.